2014
DOI: 10.1021/bi500916y
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Mechanistic, and Spectroscopic Characterization of Metallo-β-lactamase VIM-2

Abstract: This study examines metal binding to metallo-β-lactamase VIM-2, demonstrating the first successful preparation of a Co(II)-substituted VIM-2 analogue. Spectroscopic studies of the half- and fully metal loaded enzymes show that both Zn(II) and Co(II) bind cooperatively, where the major species present, regardless of stoichiometry, are apo- and di-Zn (or di-Co) enzymes. We determined the di-Zn VIM-2 structure to a resolution of 1.55 Å, and this structure supports results from spectroscopic studies. Kinetics, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
69
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 74 publications
12
69
1
Order By: Relevance
“…CcrA*(49/233) behaves in an analogous manner to CcrA*(49/126). Previous stopped-flow kinetic studies with CcrA (and other MβLs) showed that no detectable product is formed at 10 ms [16, 24, 54, 55, 5759], and it is, therefore, tempting to assign the shorter of the two distances in CcrA*(49/126) and (49/233) to unreacted enzyme, though it is entirely possible that a second intermediate is present, albeit one in which the distances between residues 49, and 126 and 233, respectively, remain unchanged. Such an intermediate may correspond to substrate forming an initial complex prior to loop movement and binding at the active site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CcrA*(49/233) behaves in an analogous manner to CcrA*(49/126). Previous stopped-flow kinetic studies with CcrA (and other MβLs) showed that no detectable product is formed at 10 ms [16, 24, 54, 55, 5759], and it is, therefore, tempting to assign the shorter of the two distances in CcrA*(49/126) and (49/233) to unreacted enzyme, though it is entirely possible that a second intermediate is present, albeit one in which the distances between residues 49, and 126 and 233, respectively, remain unchanged. Such an intermediate may correspond to substrate forming an initial complex prior to loop movement and binding at the active site.…”
Section: Discussionmentioning
confidence: 99%
“…The B3 enzymes have the same metal binding sites as the B1 enzymes except that Cys221 is replaced with a conserved histidine, and include MβL L1 from Stenotrophomonas maltophilia [13]. The B1 and B3 enzymes most often require two bound Zn(II) ions for full catalytic activity [1416]. The diversity of the MβLs is best exemplified by the enzymes’ vastly differing susceptibilities towards inhibitors [4, 5, 7, 8, 1723], metal binding properties (cooperative versus sequential) [15], and reaction mechanisms ( i.e., whether a ring-opened nitrogen anionic intermediate is formed when using nitrocefin or chromacef as substrate (Scheme 1)) [24].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that a small amount of a short-lived intermediate has recently been described for the hydrolysis of chromacef by VIM-2 [41]. Although speculative at this point, the lack of any traceable intermediate reported herein might be a consequence of the concentration of the enzyme (20 M, in contrast to 80 M utilized in [41]) being too low to observe a putative short-lived nitrocefin intermediate.…”
Section: Stopped-flow Analysis Of Vim-2 Inhibition By Poly-argininementioning
confidence: 57%
“…In structures of dizinc B1 MBLs with differing affinities for each site, Zn1 is typically refined with higher average occupancy than Zn2, consistent with biochemical studies assigning Zn2 as the more weakly binding site [66-69]. In other B1 MBLs, the dizinc site has been shown to bind both zinc ions with positive cooperativity, with binding of the first equivalent enhancing binding of the second (reviewed in [70]). Some crystal structures of the B1 β-lactamase NDM-1 also reveal a third zinc ion (Zn3) bound at the edge of the active site, positioned approximately 8 Å from the dinculear zinc cluster [71].…”
Section: Common Structural Featuresmentioning
confidence: 70%
“…In substrates with electron withdrawing groups conjugated to this nitrogen (e.g. the cephems nitrocefin and chromacef), the nitrogen anion is strongly stabilized and protonation of this anionic intermediate, observed through kinetic, spectroscopic, and isotope effect techniques, is the rate limiting step in the overall reaction [70, 132, 147-149]. This protonation does not appear to be mediated by an amino acid side chain [105].…”
Section: Substrate Binding Catalysis and Inhibitor Designmentioning
confidence: 99%